Willingness to Embrace COVID-19 Vaccination Amongst Residents in a Low-Income Nation: Insights From a Cross-Sectional Study on a Limited Cohort - Manaye Tamrie Derseh BPharm, MSc; Abyou Seyfu Ambaye BPharm, MSc; Ashagrachew Tewabe Yayehrad BPharm, MSc; Abinet Abebe BPharm, MSc; Yohannes Wobie BPharm, MSc; Erkihun Assefa BPharm, MSc (SAGE Publishing, 2024)
The global pandemic had a significant impact on countries around the world, both politically and socioeconomically. It is crucial that swift decisions and actions need to be taken to prevent negative outcomes. The development of vaccines has emerged as a potential necessity for countries worldwide. Ethiopia began vaccinating health professionals and high-risk individuals in March 2021, according to a report from the World Health Organization citing the Ethiopian Federal Ministry of Health. This study aimed to assess the determinants of willingness to receive the COVID-19 vaccine among Debre Markos city administration residents. A community-based cross-sectional study design was employed to recruit 845 individuals as a sample. Descriptive statistics and logistic regression were used as statistical analysis techniques. Among the total 845 samples, the overall response rate was 98.34%. Two hundred forty-two participants showed their willingness to receive vaccines. Age (AOR = 2.56; 95%CI = [1.87-3.23]), sex (Female) (AOR = 3.45; 95% CI = [2.07-5.26]), having children (AOR = 1.21; 95% CI = [1.02-1.90]), and Chronic Disease (AOR = 2.98; 95% CI = [1.67-3.50]) were significantly and positively associated with willingness to receive COVID 19 vaccines at 95% CI. Although most of the participants were aware of the possibility of COVID-19 to cause fever; and its transmission, only a small percentage of the total participants showed their willingness to receive the vaccine if it was available to them. Elderly and individuals with chronic diseases need to get a priority of taking those vaccinations.